Studi Korelasi antara Keterampilan Digital dan Sikap Guru dalam Integrasi Pembelajaran berbasis Information and Communication Technology (ICT) di Sekolah Menengah: Penelitian - Putri Rahma Dianti; Rizka Amalia Putri; Asih Rahayu Ajeng Agesti; Surtika (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This article aims to analyze the relationship between ICT skills and teachers' attitudes toward the integration of ICT-based learning in secondary schools. The implementation of ICT-based learning in schools is an effort to enhance the use of technology and improve teacher competencies. This research employed a descriptive correlational design using a survey method. The sample consisted of 50 teachers selected through simple random sampling using an online picker wheel method. Data analysis was conducted using an Independent T-test, while the relationships between variables were analyzed using partial correlation tests. The results of the study indicate a significant correlation (p < 0.05) between ICT skills and teachers' attitudes toward ICT integration in classroom learning. Teachers with higher ICT skills tend to have more positive attitudes and are more capable of effectively implementing technology in the learning process. These findings highlight the importance of strengthening teachers’ digital competencies as a prerequisite for the successful implementation of ICT-based learning in schools.